Factores asociados al uso rutinario de episiotomía en gestantes nulíparas atendidas en el Hospital Iquitos “César Garayar García”, 2023 - Vásquez Mendoza, Silvia Virginia (2024)
Objectives: To determine the factors associated with the routine use of episiotomy in nulliparous pregnant women attended at the Hospital Iquitos "César Garayar García" during the period January - December 2023. Methods: Observational, analytical, cross-sectional and retrospective study. Results: The prevalence of episiotomy was 67.6%, where 63.9% were adolescent pregnant women (mean = 19 years; ± SD = 3.3); 75.7% had high school education; 79.3% were cohabitants and 88.8% were from urban districts. In addition, 78.1% had adequate prenatal care; in 86.4% the gestation was at term; 85% had spontaneous vaginal birth; 98% had a second stage of labor lasting less than one hour; 9.5% had perineal tears; in 6.5% the total bleeding during labor was ≥500cc. Also, 95.3% of episiotomies were performed by obstetricians; 69.8% had no justified indication for episiotomy; 97% had mediolateral episiotomy; and 91.7% had no complications due to episiotomy. Among the neonates, 89.9% were at term; 92.3% had normal birth weight; 76.9% had normal head circumference and 97% had a first minute Apgar ≥ 7 points. In the association analysis, only prenatal care and perineal tears were significantly associated with episiotomy. Conclusions: A high prevalence of episiotomy was found in nulliparous women, sociodemographic, obstetric and neonatal factors were identified, and an association was found with prenatal care and perineal tears.